The origin of storms - Bear, Elizabeth (The Lotus Kingdoms ;, 2022)
"Hugo Award-winning author Elizabeth Bear returns to conclude her acclaimed epic fantasy trilogy of the Lotus Kingdoms, which began with The Stone in the Skull and The Red-Stained Wings, bringing it all to a surprising, satisfying climax in The Origin of Storms. The Lotus Kingdoms are at war, with four claimants to the sorcerous throne of the Alchemical Emperor, fielding three armies between them. Alliances are made, and broken, many times over-but in the end, only one can sit on the throne. And that one must have not only the power, but the rightful claim"--